2016
DOI: 10.1016/j.ydbio.2016.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate receptor-1 in cardiomyocytes is required for normal cardiac development

Abstract: Sphingosine 1-phosphate (S1P) is a bioactive lipid that acts via G protein-coupled receptors. The S1P receptor S1P1, encoded by S1pr1, is expressed in developing heart but its roles there remain largely unexplored. Analysis of S1pr1 LacZ knockin embryos revealed β-galactosidase staining in cardiomyocytes in the septum and in the trabecular layer of hearts collected at 12.5 days post coitus (dpc) and weak staining in the inner aspect of the compact layer at 15.5 dpc and later. Nkx2-5-Cre− and Mlc2a-Cre−mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 38 publications
3
38
0
1
Order By: Relevance
“…Numerous cardiac cell types respond to the S1P-S1P1 signaling pathway, however, the specific role of S1P1 in each cell type has not been fully examined. A recent study showed that deletion of S1P1 from cardiomyocytes leads to decreased number of cardiomyocytes in the ventricular compact layer19. Interestingly, while investigating the role of S1P1 in the development of the kidney vasculature we found that deletion of S1P1 in SCL + precursors led to bradycardia, suggesting an indispensable role of S1P1 in SCL + progenitors during heart development15.…”
mentioning
confidence: 70%
“…Numerous cardiac cell types respond to the S1P-S1P1 signaling pathway, however, the specific role of S1P1 in each cell type has not been fully examined. A recent study showed that deletion of S1P1 from cardiomyocytes leads to decreased number of cardiomyocytes in the ventricular compact layer19. Interestingly, while investigating the role of S1P1 in the development of the kidney vasculature we found that deletion of S1P1 in SCL + precursors led to bradycardia, suggesting an indispensable role of S1P1 in SCL + progenitors during heart development15.…”
mentioning
confidence: 70%
“…Global and endothelial-specific knockout of S1pr1 in mice causes abnormal vessel development and death at midgestation due to defective sprouting angiogenesis [3,[7][8][9]. We showed that cardiomyocyte-specific loss of S1pr1 during development led to ventricular septal defects and ventricular noncompaction [6]. These structural abnormalities caused perinatal death in 68% of mutant mice; however, the remaining S1pr1 cardiomyocyte mutant mice survived to adulthood [6].…”
Section: Introductionmentioning
confidence: 83%
“…Dr. Xu Peng (Scott & White Memorial Hospital, Temple, USA) provided Mlc2a-Cre knockin mice (Myl7 tm1(cre)Krc , designated as Mlc2a Cre/+ ) [21]. Mice with conditional deletion of S1pr1 were generated as previously described [6]. We used Mlc2a Cre/+ rather than Mlc2v Cre/+ due to more efficient Cre-mediated excision in embryonic ventricular cardiomyocytes using Mlc2a Cre/+ [6,22].…”
Section: Mouse Strainsmentioning
confidence: 99%
See 2 more Smart Citations